2015
DOI: 10.1097/qad.0000000000000941
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of treated HIV-1 positive individuals according to viral subtype in Europe and Canada

Abstract: Objectives:To estimate prognosis by viral subtype in HIV-1-infected individuals from start of antiretroviral therapy (ART) and after viral failure.Design:Collaborative analysis of data from eight European and three Canadian cohorts.Methods:Adults (N>20 000) who started triple ART between 1996 and 2012 and had data on viral subtype were followed for mortality. We estimated crude and adjusted (for age, sex, regimen, CD4+ cell count, and AIDS at baseline, period of starting ART, stratified by cohort, region of or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
0
5
1
Order By: Relevance
“…[48,49] As a result, most studies indicate that individual ARVs and standard ART regimens are equally effective, regardless of HIV subtype. [50][51][52] In this study, the HIV-1-subtype and acquisition of HIVDRM were not significantly associated. In contrast, some studies showed that women and infants infected with HIV-subtype C were more likely to develop NVP resistance than other HIV subtypes.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…[48,49] As a result, most studies indicate that individual ARVs and standard ART regimens are equally effective, regardless of HIV subtype. [50][51][52] In this study, the HIV-1-subtype and acquisition of HIVDRM were not significantly associated. In contrast, some studies showed that women and infants infected with HIV-subtype C were more likely to develop NVP resistance than other HIV subtypes.…”
Section: Discussioncontrasting
confidence: 61%
“…Antiretroviral drugs have generally proven to be effective against a wide range of HIV subtypes, despite being primarily tested in people with subtype B [48,49] . As a result, most studies indicate that individual ARVs and standard ART regimens are equally effective, regardless of HIV subtype [50–52] . In this study, the HIV-1-subtype and acquisition of HIVDRM were not significantly associated.…”
Section: Discussionmentioning
confidence: 58%
“…A relatively consistent finding is that compared with genotype A, genotype D is associated with mortality before ART 6 8 . Research on HIV-1 subtypes and ART showed that infection with genotype A results in increased mortality compared to that with genotype B in Europe and Canada 9 . In China, studies showed that CRF01_AE is associated with faster disease progression from estimated seroconversion to acquired immune deficiency syndrome (AIDS) compared with non-CRF01_AE in ART-naïve patients 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations have found that the distribution of HIV-1 subtype is correlated with infectious route and region. 2 In China, 47% CRF07_BC was concentrated in men who have sex with men. 20 Of all CRF08_BC, 67% were found in patients infected HIV through heterosexual contact and 23% through injecting drug use.…”
Section: Discussionmentioning
confidence: 99%
“… 1 Monitoring the subtype-specific differences in long-term clinical outcomes during ART can help reduce mortality. 2 4 Globally, the most prevalent HIV-1 subtype is C (46.6%), followed by B (12.1%), A (10.3%), CRF02_AG (7.7%), CRF01_AE (5.3%), G (4.6%), and D (2.7%). 5 A previous systematic review conducted in ART-naive patients suggested that HIV-1 subtypes C and D were the most aggressive in disease progression, followed by G, CRF01_AE, and CRF02_AG.…”
Section: Introductionmentioning
confidence: 99%